2013
DOI: 10.1136/neurintsurg-2012-010629
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy with the Solitaire device in acute basilar artery occlusion

Abstract: Mechanical thrombectomy with the Solitaire FR device can rapidly and effectively contribute to a high rate of recanalization and improve functional outcome in patients with ABAO and has an acceptable complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
47
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 25 publications
9
47
3
Order By: Relevance
“…Recent studies with the use of mechanical thrombectomy with stent retrievers reported significantly increased recanalization rates ranging from 74 -100% in patients with acute BAO. [12][13][14] In our study, we achieved successful recanalization (TICI grades 2b to 3) in 96% (24/25) of patients, which is in line with previous reports. Successful recanalization with only the Solitaire stent occurred in 84% (21/25) of patients.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Recent studies with the use of mechanical thrombectomy with stent retrievers reported significantly increased recanalization rates ranging from 74 -100% in patients with acute BAO. [12][13][14] In our study, we achieved successful recanalization (TICI grades 2b to 3) in 96% (24/25) of patients, which is in line with previous reports. Successful recanalization with only the Solitaire stent occurred in 84% (21/25) of patients.…”
Section: Discussionsupporting
confidence: 80%
“…[12][13][14] In contrast to our study, these previous studies included patients treated within 24 hours of stroke symptom onset. In a series of 14 patients treated with a Solitaire thrombectomy, Mordasini et al 12 reported that 28.6% (4/14) had a good outcome (mRS 0 -2), and the mortality rate was 35.7% (5/14).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations